“Come on! He Has Never Cooked in His Life!” New Alternative Masculinities Putting Everything in Its Place - Valls-Carol, Rosa; Madrid-Pérez, Antonio; Merrill, Barbara; Legorburo-Torres, Guillermo (Frontiers in Psychology, 2021)
Communicative acts of some women are perpetuating the dominance that DTM (Dominant Traditional Masculinities) have over both women and OTM (Oppressed Traditional Masculinities). Some women use language in a disdainful manner to reprimand oppressed men’s behavior in daily life situations, the same behavior that such women would not reproach to DTM. But NAM (New Alternative Masculinities) are reacting to this. This article analyzes the communicative acts employed in all these situations, both those produced by women and DTM, as well as NAM’s communicative acts in response to those offenses. Data was collected using communicative daily life stories of give women and three men with diverse profiles and different levels of participation in women’s and men’s movements. Findings highlight, from the transformative dimension of the communicative methodology, that the use of language of desire in NAM’s reactions is effective not only to make justice with men who have never executed violence on women, but also to undermine the attractiveness of both DTM’s behavior and the comments of some women on such behavior. These findings complement previous research on preventive socialization of gender violence by broadening scientific knowledge on NAM’s communicative acts that prevent and eradicate gender-based violence. Further research ought to broaden the evidence of how some women who defend feminist values sometimes do not support and even tease or reprimand men who practice these values; moreover, an important line could analyze the way people talk about men with NAM attitudes to hold back reprimands in comparison to how people talk about men who follow a DTM model.